Imaging of Carpal Instabilities - Grunz, Jan-Peter; Gietzen, Carsten Herbert; Grunz, Katharina; Bley, Thorsten; Schmitt, Rainer (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Background The term “carpal instability” describes different debilitating wrist conditions, in which the carpus is unable to maintain its physiological range of motion and load transfer. Depending on the cause and location of the dysfunction, four groups can be defined: dissociative, non-dissociative, complex, and adaptive carpal instability. As the most common form by far, dissociative carpal instability can further be categorized as dorsal or palmar intercalated segment instability, contingent on the afflicted interosseous ligament.Method This review article outlines the different entities of carpal instability, their pathophysiology, and their clinical presentation. It further discusses the diagnostic significance of different imaging methods as well as the established treatment options for each form of instability in context with the current literature.Results and Conclusion Early detection and treatment of carpal instability are essential for preventing carpal osteoarthritis. Traumatic lesions of the scapholunate interosseous ligament are the most frequent cause of instability. They can occur in an isolated fashion or in context with other carpal injuries. While stress imaging and fluoroscopy facilitate the differentiation between dynamic and static forms of carpal instability, only MRI and CT/MR arthrography can directly reveal the extent of ligament discontinuity.Key Points:Citation Format
Keywords: arthrography; hand; radiography; MR imaging